A fast numerical method for internal flood water dynamics to simulate water on deck and flooding scenarios of ships - Janßen, Christian Friedrich; Bengel, Sebastian; Rung, Thomas; Dankowski, Hendrik (Volume 5: Ocean Engineering, 2013)
The paper reports the extension of a Lattice Boltzmann model for the nonlinear viscous shallow water equations (NSW) and its application to the simulation of internal flood water dynamics. The solver is accelerated with the help of NVIDIAs CUDA framework to access the computational power of graphics processing units (GPGPUs). The model is validated with typical tank sloshing and cross flooding scenarios and the results are compared to analytical solutions and the results of a state-of the art shallow water solver on the basis of Glimm's method.